Sex and age are associated with host immune responses and multi-organ dysfunction in hospitalized patients with COVID-19 - Guochao Zhang; Yingying Zhao; Xiaoxia Chang; Qi Gao; Yunchao Zhang; Yanjun Lai (Frontiers in Public Health, 2026)
Objectives Sex- and age-related disparities are independent risk factors for poor COVID-19 outcomes, but underlying mechanisms remain unclear. Methods This retrospective cohort study included 395 hospitalized COVID-19 patients (December 2022–March 2023). Biomarkers of multi-organ injury and immune responses were analyzed to evaluate the impact of sex and age on disease progression and clinical outcomes. Normality was assessed with the Shapiro–Wilk test; Student’s t or Mann–Whitney U tests were used accordingly, with Benjamini-Hochberg false discovery rate correction across 45 biomarkers. Multivariable logistic regression was used to adjust for sex, age, co-infection, comorbidities, and symptom onset to discharge time. Results Among 395 patients (68% mild, 32% severe), males accounted for 76% of severe cases and patients aged ≥75 years for 79%. After false discovery rate correction ( q < 0.05), 37 of 45 biomarkers differed by severity, 24 by sex, and 22 by age. Male patients had higher inflammatory, coagulation, cardiac, hepatic, and renal injury markers and lower lymphocyte, total protein, and albumin levels. Although not statistically significant, T, B, or NK cell counts showed decreasing trends in males. Older adult male patients displayed the most pronounced inflammatory responses, coagulation abnormalities, multi-organ injury, lymphopenia, and reduced nutritional reserves. In multivariable logistic regression, male sex (OR 1.925, 95% CI 1.063–3.484, p = 0.031) and age ≥75 years (OR 5.164, 95% CI 2.733–9.756, p < 0.001) were associated with severe COVID-19; the male sex and age association persisted after excluding co-infections and in patients with shorter onset-to-discharge durations. Conclusion Sex and age differences are closely associated with COVID-19 severity, likely due to multi-organ dysfunction and immunosuppression following SARS-CoV-2 infection.